Α-synuclein-lanthanide metal ions interaction: binding sites, conformation and fibrillation. Issue 1 (December 2015) - Bai, Jia; Zhang, Zeting; Liu, Maili; Li, Conggang
Abstract Background The pathological hallmark of Parkinson's disease is the deposition of cytoplasmic neuronal inclusions termed Lewy bodies. The major component of Lewy bodies is amyloid fibrils of α-synuclein. To investigate what causes α-synuclein aggregation is essential to understand its pathological roles in Parkinson's disease. Various metal ions, including iron and copper, have been implicated in the pathogenesis of Parkinson's disease. Divalent metal ions can regulate α-synuclein fibrillation rate, however, few studies have been performed to investigate how trivalent metal ions interact with α-synuclein and their effect on α-synuclein fibrillation. The study of the interaction between divalent and trivalent metal ions with α-synuclein is of vital importance to realize the mechanism of α-synuclein fibrillation. Results Here we used nuclear magnetic resonance spectroscopy to determine the trivalent metal ions (lanthanides) binding sites in α-synuclein. We found that lanthanide metal ions not only bind non-specifically to the C-terminal domain of α-synuclein, but also transiently interact with residues contain carboxyl groups in the N-terminal and NAC regions, the latter binding sites were not found for divalent cations. In addition, lanthanide ions bound α-synuclein exhibits slower conformational exchange rate. Compare to divalent cations, lanthanide ions accelerate α-synuclein fibrillation much faster. Conclusions We identified the lanthanide metal ions binding sites in α-synuclein and found a hierarchal effect for lanthanide ions binding to α-synuclein, driven by the interaction with aspartic acids and glutamic acids residues. Lanthanide ions binding also induced conformational dynamics change of α-synuclein. Compared to divalent cations, lanthanide metal ions significantly accelerated α-synuclein fibrillation, possibly due to the different inherent properties such as charge, binding sites and coordination modes.